2015
DOI: 10.3354/dao02873
|View full text |Cite
|
Sign up to set email alerts
|

Specific PCR for Myxobolus arcticus SSU rDNA in juvenile sockeye salmon Oncorhynchus nerka from British Columbia, Canada

Abstract: A PCR for the specific detection of the salmon brain parasite Myxobolus arcticus (Pugachev and Khokhlov, 1979) was developed using primers designed to amplify a 1363 base pair fragment of the small subunit rDNA. The assay did not amplify DNA from 5 other Myxobolus species or from 7 other myxozoan species belonging to 5 other genera. For juvenile sockeye salmon Oncorhynchus nerka (Walbaum) collected from Chilko Lake, British Columbia (BC), Canada, in 2011, the prevalence by PCR was 96%, in contrast to 71% by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…2 for zone definitions); n = number tested; PCR+: number positive by polymerase chain reaction the anterior spinal cord or hindbrain of sockeye salmon that elicits negligible overt pathology. Our finding of M. arcticus in 27 to 66% of juvenile Fraser River sockeye collected from the Strait of Georgia over 3 yr was consistent with Mahony et al (2015), who reported the parasite in 53 and 71% of histological brain preparations from juvenile sockeye salmon collected at the Chilko Lake smolt fence in 2010 and 2011, respectively. Nearly all (96%) of the latter group were found to be infected by using PCR (Mahony et al 2015).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…2 for zone definitions); n = number tested; PCR+: number positive by polymerase chain reaction the anterior spinal cord or hindbrain of sockeye salmon that elicits negligible overt pathology. Our finding of M. arcticus in 27 to 66% of juvenile Fraser River sockeye collected from the Strait of Georgia over 3 yr was consistent with Mahony et al (2015), who reported the parasite in 53 and 71% of histological brain preparations from juvenile sockeye salmon collected at the Chilko Lake smolt fence in 2010 and 2011, respectively. Nearly all (96%) of the latter group were found to be infected by using PCR (Mahony et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding of M. arcticus in 27 to 66% of juvenile Fraser River sockeye collected from the Strait of Georgia over 3 yr was consistent with Mahony et al (2015), who reported the parasite in 53 and 71% of histological brain preparations from juvenile sockeye salmon collected at the Chilko Lake smolt fence in 2010 and 2011, respectively. Nearly all (96%) of the latter group were found to be infected by using PCR (Mahony et al 2015). There was no evidence in the present study for trends in the prevalence of M. arcticus among catch areas in the Strait of Georgia during the 6−8 wk residency of juvenile sockeye within the Strait of Georgia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, this approach can be time-and laborconsuming, and detection and identification is mainly based on the mature spore stages, with the early parasite stages likely to be neglected (Grabner et al 2012, Mahony et al 2015. Immunological methods based on antibodies or lectins (Knaus & El-Matbouli 2005, Estensoro et al 2013) have also been developed.…”
Section: Introductionmentioning
confidence: 99%